(3TQGFY GdGSdGe aj eSGFd GdMdGd hGdMQGes - (3fLe GdOjf CHj GdbGSe LYaQ Hf GdMSf Hf SYjO GdMdjs
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI Gddge Efj GMeOc MeOkG jbd aj GfJTGQg MeO cd MGeO GeG HYO aEf QYGjI GdGjeGf JhLH bVGA Mb GdGNhGf SGdfj Cf Cedj Ydjg eNJUQkG aj GdGMcGe s
(3BNQgG (B:s
(3hMjK CJjfG HeG bUOfGg hhajfG HeG hYOfG adfMeO Gddg GdPj LYdfG YfO JHOO GddGghGA hJYOO GdGQGA ef GdeJeScjf s
(3heUfagG ef TjhN GdTjYI GdcHGQ hGdUMjM Gfg LeGd GdOjf GdMdjs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GjQGf (B- (3eQcR cJHNGfI (B(703) s
Keywords: (3eJaQbGJs